(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2021)
Although tuberculosis (TB), caused by the bacteria Mycobacterium tuberculosis, affects the lungs in the majority of cases, it can also affect other parts of the body. It is most common in young children and HIV-infected patients, but it can also be found in adults with the condition. The most severe form of tuberculosis, tuberculous meningitis (TBM), is associated with the highest mortality and morbidity rates when compared to other forms of tuberculosis. Despite anti-tuberculosis treatment, tuberculosis-related mortality (TBM) remains a leading cause of death. TBM is difficult to diagnose early using immune-based and molecular-based methods because of the non-specific symptoms that occur in the disease and the low number of bacteria present in the target area, particularly the cerebrospinal fluid (CSF). TBM patients have a high sensitivity and specificity for tuberculosis, but there is currently no established diagnostic method that can detect the infection with high accuracy in a timely manner. In addition, the emergence of drug-resistant Mycobacterium tuberculosis strains complicates the diagnosis and treatment regimen for tuberculous bronchitis. It is the purpose of this review to summarise the difficulties associated with the currently employed molecular-based diagnostic methods as well as the potential future application of molecular diagnostic methods for TBM.